Targeted knockout of phospholipase A2 to increase lipid productivity in Chlamydomonas reinhardtii for biodiesel production. (January 2019) - Shin, Ye Sol; Jeong, Jooyeon; Nguyen, Thu Ha Thi; Kim, Jaoon Young Hwan; Jin, EonSeon; Sim, Sang Jun
Highlights: An efficient way of genome editing using CRISPR-Cas9 in microalgae. Knockout of a key effector gene in Lands cycle have increased in TAG accumulation. Increase in overall lipid productivity of the green alga, Chlamydomonas reinhardtii. Upstream process for reducing the production cost of the microalgal biofuel. Abstract: Biofuel derived from microalgae have several advantages over other oleaginous crops, however, still needs to be improved with its cost aspect and can be achieved by developing of a strain with improved lipid productivity. In this study, the CRISPR-Cas9 system was incorporated to carry out a target-specific knockout of the phospholipase A2 gene in Chlamydomonas reinhardtii . The targeted gene encodes a key enzyme in the Lands cycle. As a result, the mutants showed a characteristic of increased diacylglycerol pool, followed by a higher accumulation of triacylglycerol without being significantly compensated with the cell growth. As a result, the overall lipid productivities of phospholipase A2 knockout mutants have increased by up to 64.25% (to 80.92 g L −1  d −1 ). This study can provide crucial information for the biodiesel industry.